2019
DOI: 10.1002/adma.201803524
|View full text |Cite
|
Sign up to set email alerts
|

Recent Progress of the Lifetime of Organic Light‐Emitting Diodes Based on Thermally Activated Delayed Fluorescent Material

Abstract: that satisfy the physical parameters of the OLEDs, and this could be assisted by the use of organic materials. Therefore, organic materials have played a key role in extending the lifetime of OLEDs. In particular, host materials and emitters in the emitting layer have been the major contributors to the improved lifetime of OLEDs, although charge transport materials such as hole and electron transport materials, exciton blocking materials, and carrier injection layers have also supported their extended lifetime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
213
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 249 publications
(215 citation statements)
references
References 59 publications
(70 reference statements)
1
213
0
1
Order By: Relevance
“…Singlets and triplets are allowed and forbidden to recombine, respectively, due to spin selection rule. It has been shown that the triplets can be almost 100% converted into singlets in thermally activated delayed fluorescence (TADF) molecules based on the design of chemically combining donor and acceptor moieties to enable intramolecular charge‐transfer states . Recently, various TADF‐molecule‐based OLEDs with extremely high external quantum efficiency (EQE) exceeding 35% have been successfully demonstrated .…”
mentioning
confidence: 99%
“…Singlets and triplets are allowed and forbidden to recombine, respectively, due to spin selection rule. It has been shown that the triplets can be almost 100% converted into singlets in thermally activated delayed fluorescence (TADF) molecules based on the design of chemically combining donor and acceptor moieties to enable intramolecular charge‐transfer states . Recently, various TADF‐molecule‐based OLEDs with extremely high external quantum efficiency (EQE) exceeding 35% have been successfully demonstrated .…”
mentioning
confidence: 99%
“…The idea was to reduce the energy gap between the singlet and triplet excited states, favouring the process known as thermally activated delayed fluorescence (TADF). The aforementioned linker was used in the synthesis of a Zr-based MOF, which retains the TADF properties of the linker, having this special importance for its promising potential to be applied in the next generation of light-emitting diodes [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…The intrinsic degradation of OLEDs is mainly ascribed to the chemical deterioration of organic (or metal-organic) materials. [4][5][6][7][8][9] Many undesired (photo)physical processes could induce such chemical deterioration, like exciton−polaron and exciton−exciton annihilations (EPA and EEA), in which EPA has been confirmed as a dominate mechanism. [10][11][12][13][14][15][16] In this process ( Fig.…”
Section: Introductionmentioning
confidence: 99%